Synthesis of nanoporous SnO2 anode by anodization in a rotating cylinder configuration - Ismael, Ghaidaa A.; Abbar, Ali H. (Iraqi Journal of Chemical and Petroleum Engineering, 2026)
Nanoporous-SnO₂ films were electrochemically prepared via anodizing of metallic tin electrodeposited on a cylindrical copper substrate using rotating cylinder electrode Technique. The effects of anodizing potential (4-7V), oxalic acid (OA) concentration (0.1-0.5M), time (10-20), and rotation speed (150-450 rpm) on the electrochemical activity of SnO2 as an anode in degrading methylene blue (MB) were investigated. Results showed that increasing oxalic acid concentration gives better performance in degrading MB while increasing anodizing potential enhanced the electrode activity up to a potential of 5 V beyond which no enhancement of electrode activity towared MB degradation was noted. Longer time of anodizing has opposite effect while rotation speed enhanced the electrocatalytic activity of SnO2. The best conditions of anodizing were potential of 5 V, 0.4M OA, 15 min, and 250 rpm in which MB removal was 87.6%. Structural morphology of SnO2 prepared at the optimum conditions confirmed the conversion of tin to SnO2 with free crack structure. These results demonstrate that adopting anodizing method with rotating cylinder technique to forming SnO2 anodes is a promising strategy for constructing high-performance anodes suitable for treatment wastewaters.